CATS MODEL OF E-ASSESSMENTS FOR SOCIAL SCIENCES COURSE - Adibah, Yusuf; Farah, Zaini; Nadzirah, Yusuf (UMK Press, 2021)
The project is designed to coincide with the present-day generation that is more readily acceptable in terms of assessment methods that are parallel to their age, which is a technology-oriented age and not entirely dependent on traditional assessment methods. This project was specially created for first year students who register for the course. The CATS Model of e-assessments approach initiative is designed and aimed to correspond with the current generation and its assess method which is more acceptable to their age, particularly a technologically advanced method that is not fully reliant on traditional evaluation methods. As previously stated, this project is prepared specifically for first-year students enrolled in the Introduction to Social Sciences course.